ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI PALLET KAYU DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - Janna, Shalia; Nobel, Aqualdo; Deny, Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The role of the industrial sector in regional economic development is able to produce goods and services with higher added value in a variety of certain commodities. In the processing industry, wood is one of the widely used raw materials. With the use of wood as raw materials and in accordance with its purpose wood can be used as decorative, functional and structural. One of the wood processed products that are widely used as industrial and trade needs is wooden pallet products. SiakHulu district is one of the areas in Kampar kabuaten with a pallet industry that is superior. this study aims to find out and analyze the factors that affect the production of wooden pallet industry in District SiakHulu Kampar Regency. The data used is primary data obtained from 5 timber pallet industries located in SiakHulu District and secondary data obtained from BPS and SiakHulu Sub-District Office. This study used multiple linear regression analysis methods to measure the influence of free variables on bound variables. The results of this study showed that variable capital, raw materials, labor, and technology have a significant effect on the production of wooden pallet industry in SiakHulu District. The dominant variable affecting production in the wooden pallet industry is the raw material variable.Keywords: Capital, Raw Materials, Labor, Technology, Production